Prevalence of Common Ear Nose and Throat Diseases in a Tertiary Care Center during Monsoon Season in Nepal - Shrestha, Kundan Kumar; Dhungana, Anup; Joshi, Rupesh Raj; Shrestha, Shivani; Mishra, Sumedh (Nepal Medical College Journal, 2025)
Ear, nose and throat (ENT) disorders contribute significantly to global morbidity and mortality, with variations in disease patterns across different regions and seasons. Nepal’s diverse climate, particularly during the rainy monsoon season, influences the prevalence of certain ENT diseases. This study aimed to assess the pattern of ENT disorders during the rainy season (monsoon) at a tertiary hospital in Nepal. A descriptive study was conducted at Nepal Medical College Teaching Hospital from June to September 2024. A total of 1042 patients aged 1 year and above were included using purposive sampling. Data was collected through clinical examinations and investigations. Statistical analysis was performed using SPSS. Among the 1042 participants, 57.77% were female, and the mean age was 31.07±18.62 years. The most prevalent ENT diseases were throat disorders (44.82%), ear disorders (44.05%), and nose disorders (11.13%). Acute pharyngitis (12.38%), acute otitis media (9.50%), and allergic rhinitis (2.87%) were the most common conditions. The study revealed an increased prevalence of acute pharyngitis, tonsillitis, acute otitis media (AOM), and allergic rhinitis during the monsoon season. This highlights the importance of early diagnosis, treatment, and preventive strategies for reducing disease burden during this period.